Predictive cultural model for family caregivers of older people with musculoskeletal pain in East Coast Malaysia: a pilot validation study - Mohd Jaias, Nurin Syafiqah; Che Abdullah, Che Azunie; Che Hasan, Muhammad Kamil; Firdaus, Mohd Khairul Zul Hasymi; Mahat, Nur Ain (IIUM Press, 2025)
Background: In Malaysia, family members play a major role in caring for the elderly as informal caregivers. Caregiving can be physically, emotionally, financially, socially, and culturally demanding. Despite these challenges, many caregivers continue to provide care because of a strong sense of family responsibility rooted in Malaysian culture and its multiethnic society. Therefore, culturally appropriate assessment tools are important to ensure valid and meaningful results across different populations. This pilot study aimed to validate the psychometric properties of the translated tools to support the development of a predictive cultural model for family caregivers.